2012
DOI: 10.1089/ten.tec.2011.0159
|View full text |Cite
|
Sign up to set email alerts
|

Micromarrows—Three-Dimensional Coculture of Hematopoietic Stem Cells and Mesenchymal Stromal Cells

Abstract: Hematopoietic stem cell (HSC) transplant is a well established curative therapy for some hematological malignancies. However, achieving adequate supply of HSC from some donor tissues can limit both its application and ultimate efficacy. The theory that this limitation could be overcome by expanding the HSC population before transplantation has motivated numerous laboratories to develop ex vivo expansion processes. Pioneering work in this field utilized stromal cells as support cells in cocultures with HSC to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 27 publications
6
51
0
2
Order By: Relevance
“…3 a,b). Thus, the long-term HSCs, which are the only cells capable of long-term self-renewal and multi-lineage potential, appear to be differentiating into more specialized progenitor cells in the static stromasupported cultures system, as previously reported [6][7][8][9] . In contrast, the number and distribution of HSCs and hematopoietic progenitor cells in the eBM cultured for up to 7 days on-chip were maintained in similar proportions to freshly harvested bone marrow (Fig.…”
Section: In Vitro Culture Of Engineered Bone Marrowsupporting
confidence: 71%
See 1 more Smart Citation
“…3 a,b). Thus, the long-term HSCs, which are the only cells capable of long-term self-renewal and multi-lineage potential, appear to be differentiating into more specialized progenitor cells in the static stromasupported cultures system, as previously reported [6][7][8][9] . In contrast, the number and distribution of HSCs and hematopoietic progenitor cells in the eBM cultured for up to 7 days on-chip were maintained in similar proportions to freshly harvested bone marrow (Fig.…”
Section: In Vitro Culture Of Engineered Bone Marrowsupporting
confidence: 71%
“…Engineering an artificial bone marrow that reconstitutes natural marrow structure and function, and that can be maintained in culture, could be a powerful platform to study hematopoiesis and test new therapeutics. It has proven difficult, however, to recreate the complex bone marrow microenvironment needed to support the formation and maintenance of a complete, functional hematopoietic niche in vitro [6][7][8][9] . Although various in vitro culture systems have (Revised NMETH-A19608) been developed to maintain and expand hematopoietic stem and progenitor cells 6-11 , there is currently no method to recreate or study the intact bone marrow microenvironment in vitro.…”
mentioning
confidence: 99%
“…Furthermore, studies have indicated that HSC--supportive properties of both human [314,330] and murine [329,341] MSC are maintained when cultured as spheroids. de Barros et al developed a 3D MSC spheroid culture system with the capacity for HSPC lodgment and proliferation [331].…”
Section: Introductionmentioning
confidence: 99%
“…CB--derived CD34 + progenitor cells were reported to attach and migrate into the MSC spheroids. In previous work, we described a high--throughput 3D spheroid co--culture system for expanding murine HSPC in the presence of MSC [341]. Spheroids were manufactured in microwell plates (AggreWell, StemCell Technologies), yielding thousands of 3D spheroids [341].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation